Feasibility of Using Palmyrah Strips as Reinforcing Material in Cost Effective Houses. (14th April 2014) - Baskaran, K.; Mallikarachchi, H. E.; Jayasekara, M. J. P. L. M.; Madushanka, G. A. T.
Abstract : Construction of cost effective houses is a dilemma among the impoverished population in developing countries. The ever increasing price of traditional building materials results in high capital investments for residential buildings. Palmyrah is a significant economic resource, widely spread all over the northeast region of Sri Lanka. This research explores the technical feasibility of using heartwood of Palmyrah as a reinforcing member in lightly loaded concrete elements. Initially, mechanical properties of Palmyrah were examined through static bending, tensile, and compressive tests. Percentages of water absorption, dimensional stability, and anchorage bond strength were investigated to envisage the suitability of Palmyrah as reinforcement. Next, several short span slabs and beams reinforced with Palmyrah strips were subjected to tests. It was observed that Palmyrah reinforcement enhanced the moment capacity of the slabs and beams compared to unreinforced sections. Experimental failure loads of slabs and beams were higher than theoretically predicted values with Palmyrah reinforcement. Further, Palmyrah reinforced beams and slabs underwent flexural failures. Thus, it is concluded that heartwood of Palmyrah has the potential to be used as reinforcement in lightly loaded slabs and beams. Further research is recommended to investigate the durability and serviceability issues.